Klitih and Street Crimes: Why Juvenile Involved in Crime? - Putri, Siti Ameenah; Faradina, Ginar Listya; Sabri, Ahmad Zaharuddin Sani Ahmad; Putri, Laras Widayati (Law Research Review Quarterly, 2023)
The spectrum of crimes within society is becoming increasingly diverse. Notably prevalent among them are street crimes perpetrated by teenagers, commonly known as "Klitih." These offenses encompass acts of abuse, physical assault, and theft accompanied by violence. Klitih crimes are often associated with high school students, and the perpetrators are typically motivated by subjective factors such as personal animosity, a quest for revenge, discontent within specific groups, or simply a desire to fill their leisure time. The characteristic feature of Klitih crimes is their association with adolescents, and these actions are frequently carried out by teenagers who are still in the throes of their high school years. The motivations behind such actions are often rooted in personal emotions and grievances. Klitih crimes occurring among students of similar age groups often involve a complex interplay of roles, wherein the victim's conduct plays a significant part. This interrelation is particularly evident in a juvenile street crime incident on Jalan Gedong Kuning, Bangutapan sub-district, Yogyakarta. Victim Precipitation, or the role of the victim, can be simplistically understood as the contribution of the victim's actions that accelerates or triggers the commission of a crime. In the Gedongkuning street incident involving Klitih actions, the victim's pursuit played a crucial role, acting as a catalyst that propelled the perpetrator to expedite their Klitih actions.